2012
DOI: 10.1111/jonm.12019
|View full text |Cite
|
Sign up to set email alerts
|

How undergraduate nursing students learn to care for patients spiritually in clinical studies - a review of literature

Abstract: Nurse leaders play a key role in keeping holistic care a nursing focus and creating a good learning environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 34 publications
(237 reference statements)
3
38
0
1
Order By: Relevance
“…For medical students, small group teaching sessions and reflective portfolios were considered the most appropriate assessment tool [21]. The same has been reported in nursing education [28,29]. Additionally, in a well-founded theory to investigate how nursing educators prepare students to assess and address spirituality, role-modeling and mentoring were also emphasized [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For medical students, small group teaching sessions and reflective portfolios were considered the most appropriate assessment tool [21]. The same has been reported in nursing education [28,29]. Additionally, in a well-founded theory to investigate how nursing educators prepare students to assess and address spirituality, role-modeling and mentoring were also emphasized [45].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some syllabuses that have previously been published share common contents. These include generic topics such as the definitions and attributes of health; the definitions of spirituality in a multidisciplinary context and its heritage in healthcare; the definition of spiritual care and ethical aspects in providing spiritual care; the influence and the impact of spirituality on patient health; the importance of spirituality in health and illness transitions; the specificity of religious aspects and the customs of the major world faiths; instruments for assessing spirituality; healthcare resources in providing spiritual care; self-awareness and own spirituality [21,28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review identified four main areas as essential for learning spiritual care: a. importance of learning in real-life situations with repeated exposure to patients in the clinical placements supported by role modeling and mentorship; b. use of pedagogical methods that assist students to understand, work with and reflect on patient's spirituality such as, reflective journals, written reflective accounts; writing care plans, which include spiritual interventions; role plays to practice spiritual assessment, including values, beliefs, and spiritual needs; group discussions on the relationship between religion, spirituality and health; analysis of case studies; reading literature and analyzing research on spirituality in illness and care; c. awareness of and overcoming conditions inhibiting spiritual care learning, such as, lack of knowledge about spirituality; uncertainty about the health care professional's role in spiritual care; unawareness about one's own spirituality; having a different faith from that of the patient; incompetence in addressing spiritual needs; lack of role models; lack of time; and work overload; and d. evaluation of students' spiritual care learning related to how students are prepared and how they are followed up after clinical studies by, for example, post clinical-reflection sessions; sharing of stories with fellow students, teachers and chaplains; supporting their learning by literature and research on spiritual care; reflective exercises and debriefing sessions to enhance safety of students and safe patient care' [51].…”
Section: Areas Essential For Learning Spiritual Carementioning
confidence: 99%
“…The presence of role models in the delivery of spiritual care and caring behaviours between staff members may enhance students' learning with a sense of belongingness in the clinical placements (McSherry 2006;Bradshaw 1997). Eventually, processing information by the help of role models and mentors may enhance students' spiritual self-development (Giske 2012) which helps them to give priority to patients' holistic needs (Baldacchino 2008), and may be transformational to both the patients and the caregivers (Dijoseph and Cavendish 2005). Thus spirituality at the workplace needs to be integrated within the multi-disciplinary team curricula to enhance their knowledge, skills and attitudes in their work relationships .…”
Section: Implications To the Education And Clinical Practicementioning
confidence: 99%